Evaluation of presynchronization and addition of GnRH at the beginning of an estradiol/progesterone protocol on circulating progesterone and fertility of lactating dairy cows - Pereira, M. H.C. [UNESP]; Wiltbank, M. C.; Guida, T. G. [UNESP]; Lopes, F. R. [UNESP]; Cappellozza, B. I.; Vasconcelos, J. L.M. [UNESP] (Elsevier, 2020)
The objectives of this study were to determine if the utilization of a presynchronization strategy would improve fertility at first artificial insemination (AI) during an E2/P4 ovulation synchronization protocol with or without GnRH administration at the beginning of the protocol. This experiment was conducted using cows (n = 665) at their first postpartum service and the following breeding treatment: CIDR insertion and 2.0 mg of estradiol benzoate (EB) on day −11; 25 mg dinoprost tromethamine (PG) on day −4; PG, CIDR withdrawal, and 1.0 mg of estradiol cypionate (ECP) on day −2; timed-AI on day 0. At 31 ± 3 days postpartum, cows were randomly allocated to one of three treatments on a weekly basis: 1) -P + GnRH: cows assigned to the breeding protocol with 100 μg of GnRH on day −11, 2) P + GnRH: cows assigned to a presynchronization protocol using CIDR insertion +2 mg EB on day −28, PG + ECP and CIDR withdrawal on day −21, and beginning of the breeding protocol plus GnRH (100 μg) on day −11, and 3) +P-GnRH: cows assigned to a presynchronization protocol and the breeding treatment without GnRH on day −11. No treatment effects were observed on P/AI at the pregnancy diagnoses on days 32 and 60, or for pregnancy losses between days 32 and 60 of pregnancy whether analyses included all cows or only cows that ovulated near TAI. Moreover, milk yield negatively affected P/AI. Cows with greater circulating P4 concentrations on day −4 had greater P/AI on day 60. Cows without CL on day −11 had a reduced P/AI and this effect was more significant in cows not treated with GnRH. Cows assigned to -P + GnRH had the lowest circulating P4 concentration on day −4 (3.4 ± 0.16 ng/mL), followed by + P-GnRH (4.56 ± 0.17 ng/mL), and +P + GnRH (5.08 ± 0.17 ng/mL) cohorts. The data of the current study suggest that the combination of a Presynch and GnRH administration at the beginning of a TAI protocol was the most effective way to increase the % of cows with a functional CL and with elevated circulating P4 concentrations at the time of PG treatment.
Keywords: Dairy cows; Fertility; Presynchronization; Progesterone; Timed-AI protocols